MONITORING SATURASI OKSIGEN DAN SUHU TUBUH MENGGUNAKAN NODEMCU BERBASIS WEBSITE PADA MARKETING OFFICE PREMIER ESTATE 2 - Anassetiya, Veby; Mufti, Mufti; Purwanto, Purwanto (Universitas Budi Luhur, 2022)
During the COVID-19 pandemic, which has not subsided, it has had a negative impact on the economic sector, one of which is in offices. In this case, the government has issued a